The humanizing in delivery: the bibliographyc study - Karla de Abreu Peixoto Moreira; Michell Ângelo Marques Araújo; Maria Veraci Oliveira Queiroz; Maria Salete Bessa Jorge; Consuelo Helena Aires de Freitas (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
This is a bibliographic study in papers of nursing of 2000 to 2005 which objective was to analysis the scientific production in nursing about humanization in delivery. It was researched seven brazilian magazines in nursing with international classification using the descriptors humanization in delivery and pain in delivery. Overall were found 16 articles which were submitted to content analysis. We highlight the core of senses that were grouped forming the categories: the rescue of historicity of delivery; the medicalization and use of technologies in delivery; humanization in delivery and methods of care to woman. The studies shown convergence of opinions about the institution of delivery and technologic interventions that get far of humanized conducts. Thus, the reversion of this phenomena occurs with respect to privacity and woman autonomy. There is need to new studies about the theme, deeming the complexity of aspects that involves the humanization in delivery.